The prisoners of Breendonk : personal histories from a World War II concentration camp - Deem, James M. (Houghton Mifflin Harcourt, 2015)
"This absorbing and captivating nonfiction account (with never-before-published photographs) offers readers an in-depth anthropological and historical look into the lives of those who suffered and survived Breendonk concentration camp during the Holocaust of World War II"--